1995
DOI: 10.1037/0735-7028.26.2.190
|View full text |Cite
|
Sign up to set email alerts
|

Effects of disclosure of comprehensive pretherapy information on clients at a university counseling center.

Abstract: This experimental study examined the effects of comprehensive versus partial written pretherapy disclosure on the behavior and perceptions of university counseling center clients. Although all clients received information on services provided, confidentiality, length of sessions, and right to terminate therapy, only the treatment group received additional information that included personalized data on therapists, what to expect in therapy, and risks and alternatives to therapy. The one statistically significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Regardless of statutory and case law, psychologists are ethically obligated to help clients make fully informed decisions about disclosing personal information in therapy on the basis of advanced knowledge of possible consequences of such disclosure (APA, 1992). There is conflicting data regarding how knowledge of limitations to confidentiality influences client disclosures in therapy (Berlin, Malin, & Dean, 1991; Braaten, Ottos, & Handelsman, 1993; Dauser, Hedstrom, & Croteau, 1995; Taube & Elwork, 1990). Nonetheless, from an ethical perspective, it is critical that clients understand the limitations to their confidentiality if they are to make informed decisions about whether to enter into treatment and whether to disclose personal information during sessions.…”
Section: Implications For Practicementioning
confidence: 99%
“…Regardless of statutory and case law, psychologists are ethically obligated to help clients make fully informed decisions about disclosing personal information in therapy on the basis of advanced knowledge of possible consequences of such disclosure (APA, 1992). There is conflicting data regarding how knowledge of limitations to confidentiality influences client disclosures in therapy (Berlin, Malin, & Dean, 1991; Braaten, Ottos, & Handelsman, 1993; Dauser, Hedstrom, & Croteau, 1995; Taube & Elwork, 1990). Nonetheless, from an ethical perspective, it is critical that clients understand the limitations to their confidentiality if they are to make informed decisions about whether to enter into treatment and whether to disclose personal information during sessions.…”
Section: Implications For Practicementioning
confidence: 99%
“…Keating and Fretz (1990) found that negative anticipations held by theologically conservative Christians about counselors can be differentially affected by explicit precounseling information that ignores (i.e., secular counselor), shows empathy with (i.e., religious-empathic counselor), or identifies with their Christian beliefs. Lewis, Davis, and Lesmeister (1983) suggested that providing potential clients with precounseling information may respond to their concerns about counseling as well as help them form more accurate expectations about counseling, and researchers have demonstrated that the use of precounseling information can help potential clients make better decisions about entering counseling (Dauser, Hedstrom, & Croteau, 1995;Lewis, Epperson, & Foley, 1989).…”
mentioning
confidence: 99%
“…The role induction process should educate the client about therapy; clarify for the client what therapy entails and what therapy is not; the clients' role in therapy, the therapist's role in therapy; as well as provide information about confidentiality, fees, and length of sessions (Dauser, Hedstrom, & Croteau, 1995). However, role induction is an aspect of therapy that is typically approached in a cursory manner (Hass, 1991).…”
Section: Role Induction To Counselingmentioning
confidence: 99%
“…Another study that explored the impact of pretherapy information on clients at a university counseling center was conducted by Dauser, Hedstrom, and Croteau (1995).…”
Section: Role Inductionmentioning
confidence: 99%